Expression of P53, HER2 and Ki67 proteins in rats subjected to bladder augmentation with stomach, colon and ileum - Miranda,Edinaldo Gonçalves de (2016)
PURPOSE: To study the expression of HER2, p53 and Ki67 proteins in cystoplasties. METHODS: Sixty rats were distributed randomly into three groups of 20 animals. Bladder augmentation was held to increase with ileum (Group I), colon (Group II) and stomach (Group III). Tissue samples of neobladder was collected from each rat to its own control. The animals were sacrificed after 12 weeks. The neobladder was withdrawn for immunohistochemitry analysis of p53, HER2 and Ki67 expression. Wilcoxon and Mann-Whitney tests were used for statistical study. RESULTS: There were no significant changes in the expression of p53 and HER2 proteins. It was observed significant increase (p<0.0001) in Ki67 expression in all groups, when compared with their respective controls. When the study groups were compared with each other, there was increase of cell proliferation in the largest gastrocystoplasties in respect of ileocystoplasties (p=0.004) and colocystoplasties (p=0.003). CONCLUSION: We observed significant increase of cell proliferation characterized by Ki67 protein in the digestive tract of the ileocystoplasties, the colocystoplasties and the gastrocystoplasties and this increase was significantly greater in gastrocystoplasties.